PENERAPAN AUDIT MODERN DI ERA TEKNOLOGI INFORMASI - Puji Astuti, Dewi Saptantinah (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2006)
Abstract Progressively information exploiting broadness and progressively share information for all decision of business, hence quality of information very is needed. To be able to provide information which with quality, needed use technology, this matter because of technology so central in assisting to yield information faster, efficient and with quality. In a condition information technology expanding like this time, accountant claimed to be able to keep abreast of the by out for study information technology. There are some reason hit is important of accountant study the the information technology, among others accountant expected not only as consumer but expected as developer a system and as auditor expected can evaluate and system, by owning the the ability hence accountant can obtainget beneficial position along with information system growth like this time. Go together information technology growth with usage computer network which progressively wide, hence transaction process also experience of change, transaction process expected faster, and progressively wide. Thereby accounting process also will experience of change, because progressively the increasing of requirement of information which quickly, wide and is accurate, hence accountancy as process to yield finance information also experience of growth Keywords: Modern Audit, Information Technology